High-reliability alloy solder capable of reducing metal element migration and preparation method of high-reliability alloy solder
By adding specific elements and composite trace elements to Sn-Ag-Cu lead-free solder and using specific processes to prepare high-reliable alloy solder, the problems of high melting point, poor mechanical properties and poor corrosion resistance of the solder are solved, and the wetting, mechanical properties and oxidation resistance of the solder are significantly improved.
Patent Information
- Application Number
- CN202510083446.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-03-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Sn-Ag-Cu lead-free solder has problems such as high melting point, poor mechanical properties and poor corrosion resistance, which limits its application in electronic packaging materials.
A high-reliability alloy solder, containing Ag 0.1-5.0%, Cu 0.1-1.0%, Sb 0.05-5.0%, Bi 0.05-4.0%, Ni 0.1-1.0%, and composite trace element A (composed of Ti, Co and B), composite trace element B (composed of P and Ge) and composite trace element C (composed of Ce, La and Nd), were prepared by specific smelting and ultrasonic dispersion processes.
It significantly improves the wetting properties, mechanical properties and oxidation resistance of the solder, reduces the migration of metal elements, and enhances the reliability of welding.
Smart Images

Figure CN119549927A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of brazing materials, and in particular relates to a high-reliability alloy solder capable of reducing metal element migration and a preparation method thereof. Background Art
[0002] With the rapid development of modern electronic technology, the miniaturization and diversification of electronic devices are becoming increasingly obvious, and the demand for electronic packaging materials is also growing. Due to the toxicity of lead, the use of traditional Sn-Pb solder is strictly restricted.
[0003] Sn-Ag-Cu lead-free solder has become the best alternative to Sn-Pb solder due to its good wettability, excellent thermal fatigue performance and other advantages. However, as a brazing material, Sn-Ag-Cu lead-free solder still has problems such as high melting point, poor mechanical properties and poor corrosion resistance, which limits its practical application.
[0004] Therefore, it is necessary to provide a corrosion-resistant Sn-Ag-Cu lead-free solder alloy and a preparation method thereof, so as to prepare a Sn-Ag-Cu lead-free solder alloy with good wettability, good mechanical properties and high oxidation resistance. Summary of the invention
[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide a lead-free solder alloy with good wettability, good mechanical properties and high oxidation resistance.
[0006] In order to achieve the above object, the present invention discloses the following technical solutions: In a first aspect, the present invention provides a high-reliability alloy solder that reduces metal element migration, wherein the solder comprises the following raw materials by mass percentage: Ag 0.1-5.0%; Cu 0.1-1.0%; Sb 0.05-5.0%; Bi 0.05-4.0%; Ni 0.1-1.0%; Complex trace elements A 0.007-0.31%; Complex trace elements B 0.001-0.13%; Complex trace elements C 0.001-0.09%; The balance is Sn and unavoidable impurities; The composite trace element A consists of Ti, Co and B; The composite trace element B consists of P and Ge; The composite trace element C consists of Ce, La and Nd.
[0007] Preferably, the mass ratio of Ti, Co and B in the composite trace element A is (0.01-0.02):1:(0.01-0.03).
[0008] Preferably, the mass ratio of P to Ge in the composite trace element B is 1:(0.33-0.46).
[0009] Preferably, the mass ratio of Ce, La and Nd in the composite trace element C is 1:(0.26-0.51):(1-2).
[0010] In a second aspect, the present invention provides a method for preparing the above-mentioned high-reliability alloy solder for reducing metal element migration, comprising the following steps: S1. Smelt Ti, Co and B in the composite trace element A with Sn according to the mass ratio to obtain Sn-Ti-Co-B master alloy, wherein Sn:Ti:Co:B=10:(0.01-0.02):1:(0.01-0.03); S2. P and Ge in the composite trace element B are smelted with Sn according to the mass ratio to obtain a Sn-P-Ge master alloy, Sn:P:Ge=10:1:(0.33-0.46); S3. Ce, La and Nd in the composite trace element C are smelted with Sn according to the mass ratio to obtain Sn-Ce-La-Nd master alloy, Sn:Ce:La:Nd=10:1:(0.26-0.51):(1-2); S4. The intermediate alloy obtained in steps S1, S2 and S3 is smelted with single metals Cu, Ag, Sb, Bi, Ni and Sn at a certain mass ratio at 950-990°C, and then the temperature is maintained for ultrasonic dispersion for 20-30 minutes. After the ultrasonic dispersion is completed, the mixture is stirred for 20-30 minutes, and finally the temperature is lowered to 490-520°C and poured into a mold to prepare the high-reliability alloy solder.
[0011] Preferably, the smelting temperature in step S1 is 1320-1340°C.
[0012] Preferably, the smelting temperature in step S2 is 1270-1290°C.
[0013] Preferably, the smelting temperature in step S3 is 1220-1240°C.
[0014] Preferably, the smelting temperature in step S4 is 940-960°C.
[0015] Preferably, the ultrasonic frequency in step S4 is 20 kHz, and the ultrasonic time is 25 min.
[0016] In the present invention: Ti plays a major role in refining grains and improving strength in solder. The addition of Ti can significantly reduce the supercooling required for solder solidification, thereby inhibiting the formation of bulk primary metal compounds. At the same time, Ti can form stable carbides (such as TiC) or borides (such as TiB2) with carbon (C) or boron (B) in the alloy. These compound particles can serve as crystal nuclei, providing additional cores for grain growth, thereby increasing the number of crystal nuclei, leading to grain refinement and improving the microstructure of the solder. In addition, Ti can also improve the wettability and flow filling of the solder, and enhance the bonding ability between the solder and the parent material. The addition of Co can improve the heat resistance and corrosion resistance of the solder, and also improve the processing properties of the solder. B can form a low-melting-point eutectic with other elements in the solder, effectively reducing the melting temperature of the solder and facilitating the brazing process. In addition, the boride formed by B can serve as a reinforcing phase in the brazing seam, improving the high-temperature strength and wear resistance of the brazing seam. The addition of B can also improve the plasticity and toughness of the solder, and reduce the brittleness of the brazed joint at high temperatures.
[0017] The main effect of trace P in lead-free solder melt is the oxygen-skin effect. P can form a dense surface protective film on the surface or subsurface of liquid solder through self-oxidation, cut off the contact between alloy solder and oxygen, reduce the surface tension of solder solution, and improve wettability. The addition of P element can change the structure of tin oxide film, forming a denser film than tin oxide film, effectively preventing oxygen from entering the lead-free solder melt, reducing the oxidation of liquid solder, and improving oxidation resistance. When the content of P element increases to a certain amount, the protective film structure formed is very perfect, and both oxidation resistance and wettability can be improved; if the content continues to increase, the oxidation resistance will no longer be enhanced. When the content exceeds a certain amount, it will become a harmful impurity, aggravate oxidation, and be detrimental to wettability.
[0018] The oxide slag in lead-free solder is mainly SnO2 and SnO, which are metal ion excess oxides (n-type semiconductors). The growth rate of n-type semiconductor oxide films is controlled by the diffusion of interstitial cations. At the same temperature, when Ge is added to the solder, the standard formation free energy of Ge oxide is lower than that of Sn oxide, and it will oxidize to GeO2 before Sn. According to the "Haffey Atomic Valence Law", after Ge is added, Ge 4+ Can ions replace Sn in the SnO lattice 2+ To maintain electrical neutrality, the gap Sn 2+ The number will decrease as Sn 2+ Reducing the concentration can reduce the oxidation rate of solder.
[0019] Electromigration refers to the phenomenon that metal ions produce mass transport along the conductor under the action of an electric field. When current passes through the conductor, an electric field force is generated, causing the metal ions to move along the direction of the electric field. Due to the migration of ions, vacancies are formed in the crystal lattice. The formation of vacancies accelerates the migration of metal ions, thereby accelerating electromigration. Electromigration of metals is a common failure mode. Electromigration of metals can cause voids and cracks in solder joints, thereby reducing the strength and conductivity of solder joints. The present invention has found that the chemical properties of rare earth elements Ce, La and Nd are very active, and due to their large atomic radius, adding them to tin and its alloys can play a role in refining grains and improving organization. Smaller grain size can reduce the number of vacancies, thereby slowing down the speed of electromigration. At the same time, rare earth elements can also improve comprehensive properties such as physical and mechanical properties to a certain extent. Ce, La and Nd under a specific ratio are added to solder to have the effect of degassing and refining alloys, and can also effectively improve the antioxidant properties of tin alloys.
[0020] Beneficial effects of the present invention: 1. The Sn-Ag-Cu lead-free solder alloy provided by the present invention has excellent wettability, mechanical properties and oxidation resistance; 2. The present invention adds rare earth elements Ce, La and Nd into the tin alloy to improve the grain size of the Sn-Ag-Cu lead-free solder alloy and reduce the electromigration of metal elements. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings required for use in the present application.
[0022] Figure 1 This is a high-power microscope image of the alloy of Example 4 at 500 times magnification; Figure 2 This is a high-power microscope image of the alloy of Comparative Example 7 at 500 times magnification; Figure 3 This is a high-power microscope image of the alloy of Comparative Example 8 at 500 times magnification; Figure 4 This is a high-power microscope image of the alloy of Comparative Example 9 at 500 times magnification; Figure 5 This is a high-power microscope image of the alloy of Example 4 at 1000 times magnification; Figure 6 This is a high-power microscope image of the alloy of Comparative Example 7 at 1000 times magnification; Figure 7 This is a high-power microscope image of the alloy of Comparative Example 8 at 1000 times magnification; Figure 8 This is a high-power microscope image of the alloy of Comparative Example 9 at 1000 times magnification. DETAILED DESCRIPTION
[0023] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0024] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0025] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0026] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0027] The technical solution of the present invention is further described in detail below in conjunction with embodiments.
[0028] Preparation of Examples Step (1), preparation of the intermediate alloy Sn-Ti-Co-B: Sn, Ti, Co and B with a purity of 99.99% are added into a powder mixing pot in a mass ratio of 10: (0.01-0.02): 1: (0.01-0.03), and grinding balls and alcohol are added. The air is exhausted and the mixture is sealed. The mixed powder is ball-milled for 2 hours, then poured out, filtered, and dried in a low-temperature vacuum. After that, it is melted at 1330° C. in an argon environment and cooled for 20 minutes to obtain a Sn-Ti-Co-B intermediate alloy. The specific element ratio is as shown in Table 1, wherein the mass ratio of the intermediate alloy A4 is not within the above ratio range of 10: (0.01-0.02): 1: (0.01-0.03), and the intermediate alloy A5 lacks Ti raw material; Table 1 Master alloy Sn-Ti-Co-B element mass ratio raw material Master Alloy A1 Master Alloy A2 Master Alloy A3 Master Alloy A4 Master Alloy A5 Sn 10 10 10 10 10.02 Ti 0.01 0.02 0.02 0.347 - Co 1 1 1 0.347 1 B 0.03 0.02 0.01 0.347 0.02 Note: “-” in the table means not added.
[0029] Step (2), preparation of Sn-P-Ge master alloy: Sn, P and Ge with a purity of 99.99% are added in a mass ratio of 10:1:(0.33-0.46) into a powder mixing pot, and grinding balls and alcohol are added, and the air is exhausted and sealed, and the mixed powder is ball-milled for 2 hours, and then poured out, filtered, and vacuum-dried at low temperature, and then smelted at 1280°C in an argon environment, and cooled for 20 minutes to obtain a Sn-P-Ge master alloy. The specific element ratio is according to Table 2, wherein the mass ratio of master alloys B4 and B7 is not within the ratio range of 10:1:(0.33-0.46), and master alloys B5 and B6 lack P and Ge raw materials respectively; Table 2 Master alloy Sn-P-Ge element mass ratio raw material Master Alloy B1 Master Alloy B2 Master Alloy B3 Master Alloy B4 Master Alloy B5 Master Alloy B6 Master Alloy B7 Sn 10 10 10 10.8 11 10.4 10 P 1 1 1 0.2 - 1 0.7 Ge 0.33 0.40 0.46 0.40 0.40 - 0.7 Note: “-” in the table means not added.
[0030] Step (3), preparation of the intermediate alloy Sn-Ce-La-Nd: Sn, Ce, La and Nd with a purity of 99.99% are added into a powder mixing pot in a mass ratio of 10:1:(0.26-0.51):(1-2), and grinding balls and alcohol are added. The air is exhausted and the mixture is sealed. The mixed powder is ball-milled for 2 hours, and then poured out, filtered, and dried in a low-temperature vacuum. After that, it is melted at 1230°C in an argon environment and cooled for 20 minutes to obtain a Sn-Ce-La-Nd intermediate alloy. The specific element ratio is as shown in Table 3, wherein the mass ratio of the intermediate alloy C8 is not within the ratio range of 10:1:(0.26-0.51):(1-2), and the intermediate alloys C5, C6 and C7 lack Ce, La and Nd raw materials respectively; Table 3 Master alloy Sn-Ce-La-Nd element mass ratio raw material Master Alloy C1 Master Alloy C2 Master Alloy C3 Master Alloy C4 Master Alloy C5 Master Alloy C6 Master Alloy C7 Master Alloy C8 Sn 10 10 10 10 11 10.45 11.5 10 Ce 1 1 1 1 - 1 1 0.983 La 0.26 0.35 0.45 0.51 0.45 - 0.45 0.983 Nd 1 1.5 1.5 2 1.5 1.5 - 0.983 Note: “-” in the table means not added.
[0031] Step (4), preparation of Sn-Cu-Ag-Sb-Bi-Ni-Ti-Co-BP-Ge-Ce-La-Nd solder alloy: the Sn-Ti-Co-B, Sn-P-Ge and Sn-Ce-La-Nd master alloys obtained in steps (1), (2) and (3), and Cu, Ag, Sb, Bi, Ni and Sn with a purity of 99.99%, are added into a melting furnace according to the mass percentage ratio in Table 4, melted at 950°C, kept warm and ultrasonically dispersed at an ultrasonic frequency of 20 kHz for 25 minutes, stirred for 25 minutes, then the surface covering and oxide slag are removed, the temperature is reduced to 500°C, and poured into a mold to prepare Sn-Cu-Ag-Sb-Bi-Ni-Ti-Co-BP-Ge-Ce-La-Nd solder alloy embodiments 1-7. The specific element mass percentages are shown in Table 4.
[0032] Table 4 Mass percentage of raw materials in Examples 1-7 raw material Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Cu 0.1 0.3 0.4 0.6 0.8 0.9 1 Ag 0.1 1 2 3 3.5 4.5 5 Sb 0.05 0.1 0.5 1 2 3 5 Bi 0.05 0.5 1 1.2 1.5 2 4 Ni 0.1 0.3 0.4 0.5 0.6 0.8 1 Master Alloy A1 0.007 - - - - - - Master Alloy A2 - 0.05 0.1 0.15 0.2 0.25 - Master Alloy A3 - - - - - - 0.31 Master Alloy B1 0.001 - - - - - - Master Alloy B2 - 0.01 0.02 0.05 0.08 0.1 - Master Alloy B3 - - - - - - 0.13 Master Alloy C1 0.001 - - - - - - Master Alloy C2 - 0.003 - - - - - Master Alloy C3 - - 0.005 0.009 0.03 0.07 - Master Alloy C4 - - - - - - 0.09 Sn Replenish to 100 Replenish to 100 Replenish to 100 Replenish to 100 Replenish to 100 Replenish to 100 Replenish to 100 Note: “-” in the table means not added.
[0033] Preparation of Comparative Examples The preparation method of the comparative example is consistent with the preparation method of the embodiment, and the specific raw materials are shown in Table 5.
[0034] Table 5 Mass percentage of raw materials in comparative examples 1-10 raw material Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Comparative Example 8 Comparative Example 9 Comparative Example 10 Cu 0.6 0.6 0.6 0.6 0.6 0.6 0.6 0.6 0.6 0.6 0.6 Ag 3 3 3 3 3 3 3 3 3 3 3 Sb 1 1 1 1 1 1 1 1 1 1 1 Bi 1.2 1.2 1.2 1.2 1.2 1.2 1.2 1.2 1.2 1.2 1.2 Ni 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 0.5 Master Alloy A2 0.15 - - 0.15 0.15 0.15 0.15 0.15 0.15 0.15 0.15 Master Alloy A4 - 0.15 - - - - - - - - - Master Alloy A5 - - 0.15 - - - - - - - - Master Alloy B2 0.05 0.05 0.05 - - - - 0.05 0.05 0.05 0.05 Master Alloy B4 - - - 0.05 - - - - - - - Master Alloy B5 - - - - 0.05 - - - - - - Master Alloy B6 - - - - - 0.05 - - - - - Master Alloy B7 - - - - - - 0.05 - - - - Master Alloy C3 0.009 0.009 0.009 0.009 0.009 0.009 0.009 - - - - Master Alloy C5 - - - - - - - 0.009 - - - Master Alloy C6 - - - - - - - - 0.009 - - Master Alloy C7 - - - - - - - - - 0.009 - Master Alloy C8 - - - - - - - - - - 0.009 Sn Replenish to 100 Replenish to 100 Replenish to 100 Replenish to 100 Replenish to 100 Replenish to 100 Replenish to 100 Replenish to 100 Replenish to 100 Replenish to 100 Replenish to 100 Note: “-” in the table means not added.
[0035] Performance Test: The solders of Examples 1-3 and Comparative Examples 1-10 were used to vacuum braze copper sheets to obtain brazed joints. The wettability, spreadability, oxidation resistance, and joint strength of the above solders were tested. The test methods and test results are as follows: (1) Wettability / spreading: Tested in accordance with GB / T 11364-2008 “Test method for wettability of solder”.
[0036] (2) Antioxidation: The present invention uses the thermogravimetric analysis function in the DTA equipment to test the antioxidant performance. The sample is a 30 mg block, the test temperature is 300 ° C, the heating rate is 10K / min, and the temperature is kept at 300 ° C for 1 hour. The test results are displayed as the percentage of sample weight gain.
[0037] (3) Joint strength: The shear strength of the brazed joint was tested using a universal testing machine.
[0038] (4) Anti-electromigration: The alloys of Example 4 and Comparative Examples 7-9 were subjected to microscopic observation. Figure 1-8 As shown, Figure 1 and Figure 5 The alloy microscopic high-power microscope images of Example 4 at different magnifications are shown below. Figure 2-4 and Figure 6-8 These are high-power microscope images of the alloys corresponding to Examples 7-9 at different magnifications.
[0039] Table 6 Performance data of Examples 1-7 and Comparative Examples 1-10 Wetting angle / ° Oxidation weight gain / % Shear strength / MPa Example 1 19.8 2.8 29.32 Example 2 18.4 2.4 30.95 Example 3 17.8 2.2 31.84 Example 4 17.1 1.8 33.61 Example 5 17.6 2.1 31.59 Example 6 18.8 2.6 30.64 Example 7 20.1 2.9 29.61 Comparative Example 1 31.7 3.7 20.76 Comparative Example 2 28.5 3.8 16.46 Comparative Example 3 26.8 4.2 26.11 Comparative Example 4 27.1 5.1 27.09 Comparative Example 5 29.4 4.9 26.37 Comparative Example 6 28.5 4.3 27.25 Comparative Example 7 31.6 3.4 21.03 Comparative Example 8 32.3 3.6 20.39 Comparative Example 9 29.0 3.5 23.65 Comparative Example 10 23.6 3.7 27.88 Result analysis: Comparison of the performance of Example 4 with Comparative Examples 1 and 2 shows that when the addition ratio of Ti, Co and B is changed or Ti is not added, the overall performance of the tin material is reduced, especially in terms of the mechanical properties of the tin material. Ti is an important alloying element. When it is added to the tin alloy, it can significantly improve the mechanical properties of the alloy, such as increasing the yield strength through solid solution strengthening and improving the microstructure of the material by refining the grains. In addition, the addition of Ti can also improve the thermal stability and corrosion resistance of the alloy, especially in applications under high temperature and high pressure environments.
[0040] From the performance comparison between Example 4 and Comparative Examples 3-6, it can be seen that when any one of P and Ge is missing or the mass ratio of P and Ge is not within a specific range, the oxidation resistance, wettability and mechanical properties of the entire tin alloy are greatly affected, especially the oxidation resistance, which is severely reduced. Therefore, the combined addition of P and Ge helps to improve the oxidation resistance of the tin alloy.
[0041] From the performance comparison between Example 4 and Comparative Examples 7-10, it can be seen that when any one of the rare earth elements Ce, La and Nd is missing or the mass ratio is not within a specific range, the oxidation resistance, wettability and mechanical properties of the entire tin material are greatly affected. Ce, La and Nd play a role in refining the grains, optimizing the interface structure, forming a strengthening phase to inhibit the generation of harmful phases, and reducing the electromigration of metal elements. At the same time, Ce, La and Nd can improve the welding strength and wettability, thereby improving the welding fatigue resistance.
[0042] Figure 1 (Example 4) shows that the grain size is small and evenly distributed, which inhibits the generation of harmful phases and has no obvious polarity effect. Figure 5 As shown; Figure 2 (Comparative Example 7) shows that the grain size is large, the distribution is disordered, and a significant polar effect and obvious harmful phases are produced, such as Figure 6 As shown; Figure 3 (Comparative Example 8) shows that the grain size is large, the distribution is disordered, and a significant polar effect and obvious harmful phases are produced, such as Figure 7 As shown; Figure 4 (Comparative Example 9) shows that the grain size is large, the distribution is disordered, and a significant polar effect and obvious harmful phases are produced, such as Figure 8 shown.
[0043] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A high-reliability alloy solder for reducing metal element migration, characterized in that: By mass percentage, the solder comprises the following raw materials: Ag 0.1-5.0%; Cu 0.1-1.0%; Sb 0.05-5.0%; Bi 0.05-4.0%; Ni 0.1-1.0%; Complex trace elements A 0.007-0.31%; Complex trace elements B 0.001-0.13%; Complex trace elements C 0.001-0.09%; The balance is Sn and unavoidable impurities; The composite trace element A consists of Ti, Co and B; The composite trace element B consists of P and Ge; The composite trace element C consists of Ce, La and Nd.
2. The high-reliability alloy solder according to claim 1, characterized in that: The mass ratio of Ti, Co and B in the composite trace element A is (0.01-0.02):1:(0.01-0.03).
3. The high-reliability alloy solder according to claim 1, characterized in that: The mass ratio of P to Ge in the composite trace element B is 1:(0.33-0.46).
4. The high-reliability alloy solder according to claim 1, characterized in that: The mass ratio of Ce, La and Nd in the composite trace element C is 1:(0.26-0.51):(1-2).
5. The method for preparing a high-reliability alloy solder for reducing metal element migration according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Smelt Ti, Co and B in the composite trace element A with Sn according to the mass ratio to obtain Sn-Ti-Co-B master alloy, wherein Sn:Ti:Co:B=10:(0.01-0.02):1:(0.01-0.03); S2. Smelting P and Ge in the composite trace element B with Sn according to the mass ratio to obtain Sn-P-Ge master alloy, Sn:P:Ge=10:1:(0.33-0.46); S3. Ce, La and Nd in the composite trace element C are smelted with Sn according to the mass ratio to obtain Sn-Ce-La-Nd master alloy, Sn:Ce:La:Nd=10:1:(0.26-0.51):(1-2); S4. The intermediate alloy obtained in steps S1, S2 and S3 is smelted with single metals Cu, Ag, Sb, Bi, Ni and Sn at a certain mass ratio at 950-990°C, and then the temperature is maintained for ultrasonic dispersion for 20-30 minutes. After the ultrasonic dispersion is completed, the mixture is stirred for 20-30 minutes, and finally the temperature is lowered to 490-520°C and poured into a mold to prepare the high-reliability alloy solder.
6. The method for preparing the high-reliability alloy solder according to claim 5, characterized in that: The smelting temperature in step S1 is 1320-1340°C.
7. The method for preparing the high-reliability alloy solder according to claim 5, characterized in that: The smelting temperature in step S2 is 1270-1290°C.
8. The method for preparing the high-reliability alloy solder according to claim 5, characterized in that: The smelting temperature in step S3 is 1220-1240°C.
9. The method for preparing the high-reliability alloy solder according to claim 5, characterized in that: The smelting temperature in step S4 is 940-960°C.
10. The method for preparing the high-reliability alloy solder according to claim 5, characterized in that: The ultrasonic frequency in step S4 is 20 kHz, and the ultrasonic time is 25 min.
Citation Information
Patent Citations
SnAgCuBi series leadless soldering tin alloy
CN101058132A
Lead-free solder for electronic packaging
CN102962599A
Solder alloy, solder ball, solder preform, solder paste and solder joint
CN111745321A
Low-silver high-reliability lead-free soft solder and preparation method and application thereof
CN113385853A
Lead-free solder
US20040115088A1